Improving Accuracy and Calibration of Deep Image Classifiers With Agreement-Driven Dynamic Ensemble - Pedro Conde; Rui L. Lopes; Cristiano Premebida (IEEE Open Journal of the Computer Society)
One of the biggest challenges when considering the applicability of Deep Learning systems to real-world problems is the possibility of failure in critical situations. Possible strategies to tackle this problem are two-fold: (i) models need to be highly accurate, consequently reducing this risk of failure; (ii) facing the impossibility of completely eliminating the risk of error, the models should be able to inform the level of uncertainty at the prediction level. As such, state-of-the-art DL models should be accurate and also calibrated, meaning that each prediction has to codify its confidence/uncertainty in a way that approximates the true likelihood of correctness. Nonetheless, relevant literature shows that improvements in accuracy and calibration are not usually related. This motivates the development of Agreement-Driven Dynamic Ensemble, a deep ensemble method that - by dynamically combining the advantages of two different ensemble strategies - is capable of achieving the highest possible accuracy values while obtaining also substantial improvements in calibration. The merits of the proposed algorithm are shown through a series of representative experiments, leveraging two different neural network architectures and three different datasets against multiple state-of-the-art baselines.